Juridical Analysis of the Mistargeted Distribution of Subsidized 3-Kilogram LPG Based on Presidential Regulation No. 104 2007 in Kudus Regency (Discourse Journal on Law and Society, 2025)
This research is motivated by the phenomenon of scarcity of 3-kilogram LPG (Liquefied Petroleum Gas) occurring in several sub-districts within Kudus Regency. This scarcity is frequently caused by misdirected distribution, wherein the subsidized gas, which pursuant to Article 3 Paragraph (1) of Presidential Regulation of the Republic of Indonesia Number 104 of 2007, is intended for low-income households and micro-enterprises, is instead accessed by middle-to-upper class individuals and sold at prices exceeding the government-mandated retail price (Harga Eceran Tertinggi/HET). The purpose of this study is to examine the implementation of the aforementioned Presidential Regulation in the distribution of 3-kg LPG within a specific sub-district of Kudus Regency, and to identify the inhibiting factors affecting its execution. This research employs a descriptive qualitative method using a field study approach. Data were collected through observation, in-depth interviews with LPG base outlet operators, sub-district government officials, and subsidy recipient residents, as well as through documentation of policies and distribution reports. The findings indicate that the implementation of the 3-kg LPG distribution policy in the field has not been conducted optimally. Many base outlets continue to sell subsidized LPG to retailers or to non-target consumers for the sake of higher profit margins, compounded by weak regulatory oversight. The impeding factors in policy implementation include: lack of understanding of the regulations by distribution actors, insufficient governmental outreach and socialization efforts, weak oversight and evaluation from Pertamina (the state-owned oil and gas company), and the absence of firm enforcement measures or sanctions against violations, which further exacerbate the problem.